2009
DOI: 10.1007/s12600-008-0020-5
|View full text |Cite
|
Sign up to set email alerts
|

Biological control potential of Turkish entomopathogenic nematodes against the Mediterranean fruit fly Ceratitis capitata

Abstract: The entomopathogenic nematodes Steinernema weiseri, S. feltiae, S. carpocapsae and two strains of Heterorhabditis bacteriophora, isolated from Turkish soils, were evaluated against larvae of the Mediterranean fruit fly (medfly) Ceratitis capitata in plastic cups under laboratory conditions with sandy loam soil and 10% moisture level. At a rate of 100 infective juveniles (IJs)/cm 2 , the last instar larvae of C. capitata were susceptible to the entomopathogenic nematodes: the S. feltiae 09-31 strain recovered f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 23 publications
4
20
2
1
Order By: Relevance
“…Interestingly, 50 IJs cm −2 was significant enough to cause more than 80% larval mortality of C. capitata, suggesting that EPN concentrations higher than 100 IJs cm −2 may cause intraspecific competition among IJs of the same EPN species or strain. This nematode concentration is lower than reported in previous studies 22,31,33 . Gazit et al 22 reported that the highest larval mortality (82.5%) of C. capitata was achieved when S. riobrave was applied at a concentration of 100 IJs cm −2 compared to other concentrations.…”
Section: Discussioncontrasting
confidence: 75%
“…Interestingly, 50 IJs cm −2 was significant enough to cause more than 80% larval mortality of C. capitata, suggesting that EPN concentrations higher than 100 IJs cm −2 may cause intraspecific competition among IJs of the same EPN species or strain. This nematode concentration is lower than reported in previous studies 22,31,33 . Gazit et al 22 reported that the highest larval mortality (82.5%) of C. capitata was achieved when S. riobrave was applied at a concentration of 100 IJs cm −2 compared to other concentrations.…”
Section: Discussioncontrasting
confidence: 75%
“…Stark and Lacey (1999) reported that the highest infection rate was caused by S. carpocapsae (65%), H. bacteriophora (50%), S. feltiae (35%), and H. marelatus (15%) against Rhagoletis indifferens larvae. Karagoz et al (2009) confirmed the effectiveness of five local EPN species against last-instar larvae of C. capitata under controlled conditions. Sirjani et al (2009) stated that S. feltiae was highly virulent against third instar larvae of Bactrocera oleae (G.) compared to S. carpocapsae, S. riobrave, S. glaseri, H. bacteriophora, and H. marelatus.…”
Section: Resultssupporting
confidence: 58%
“…The fruit fly pupae might be resistant to EPN penetration (Malan and Manrakhan, 2009). Many tested EPNs were found to (Lindegren and Vail, 1986;Yee and Lacey, 2003;Soliman, 2007 andKaragoz et al 2009). Efficacy of H. baujardi LPP7 was evaluated against the fruit fly pupae by Minas et al (2016) and recorded more than 80% mortality rate after application of 816 IJs/cm 2 .…”
Section: Pupal Bioassaymentioning
confidence: 99%
“…The difference may be attributed to nematode strain difference, host species difference, and experimental design. Karagoz et al (2009b) tested the efficiency of 5 native Turkish EPN species against last-instar C. capitata larvae under laboratory conditions. The S. feltiae 09-31 Aydın isolate was highly virulent and caused 78% mortality, whereas S. weiseri and S. carpocapsae killed 50% and 56% of the larvae, respectively.…”
Section: Discussionmentioning
confidence: 99%